Naucoridae Leach, 1815 (Insecta: Hemiptera: Nepomorpha) of Maranhão, Brazil - Viana, Renata Santos; Franco, Cleilton Lima; Azevêdo, Carlos Augusto Silva De; Stefanello, Fabiano (Zootaxa, 2025)
Naucoridae is a family of aquatic bugs found mostly in tropical and subtropical regions worldwide. There are records of five subfamilies, 11 genera, and 74 species from Brazil, with 11 species occurring in northeastern Brazil and seven in the state of Maranhão. Here, we aimed to study the naucorid fauna of Maranhão through extensive sampling. In total, 693 specimens were examined, belonging to three subfamilies, five genera, and 10 species: Australambrysus cf. acutangulus (Montandon, 1897), Carvalhoiella helenae Rodrigues & Sites, 2016, Limnocoris burmeisteri De Carlo, 1967, L. illiesi De Carlo, 1967, L. menkei La Rivers, 1962, L. minutus De Carlo, 1951, L. surinamensis Nieser, 1975, Maculambrysus sp., Maculambrysus transversus Rodrigues, Canejo & Sites, 2024, and Placomerus obscuratus Sites & Camacho, 2014. The subfamily Ilyocorinae, and the genera Carvalhoiella De Carlo, 1963 and Placomerus La Rivers, 1956, represent the first records for northeastern Brazil. Additionally, Placomerus obscuratus Sites & Camacho, 2014 is recorded for the first time in Brazil. Thus, our results increase the number of known species in this state from seven to sixteen, reducing the Wallacean and Linnean gaps in the knowledge of Naucoridae diversity.